Pasien: Konsumen Yang Unik - Thalia Prameswari; Wahyu Andrianto (Jurnal MHKI, 2022)
April 20th is celebrated as National Consumer Day, while World Patient Safety Day is celebrated every September 17th. The two commemoration days prove that consumers and patients have a fundamental position, both sociologically and legally. In Indonesia, there are several laws and regulations that provide legal protection for patients. One of them is the Law of the Republic of Indonesia Number 8 of 1999 concerning Consumer Protection. However, the question arises regarding whether the patient is a consumer as referred to in the Consumer Protection Act. This is certainly interesting to analyze so that the Law of the Republic of Indonesia Number 8 of 1999 concerning Consumer Protection can provide legal benefits, especially regarding legal protection for patients as consumers.